2015
DOI: 10.1111/ap.12086
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Clinical Competence of Psychology Students Through Objective Structured Clinical Examinations (OSCEs): Student and Staff Views

Abstract: Objective Structured Clinical Examinations (OSCEs) are a well-known, reliable, and valid assessment method used across the healthcare sector. In the present study, we applied OSCEs in three units within professional postgraduate psychology courses, with the broad aims of identifying staff and student perceptions of the assessment. At the conclusion of each OSCE, staff and students completed a feedback questionnaire that contained both scaled and open-ended questions. Results suggest that clinical psychology OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
61
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 51 publications
7
61
0
6
Order By: Relevance
“…Students' opinions regarding stress and anxiety associated with OSCEs have also been explored. 2,9,10 While OSCEs have been found to be more anxiety provoking than other assessments, 9,10 with students expressing concerns that heightened anxiety impacts OSCE performance, 2 the literature is mixed regarding the actual impact this anxiety has on OSCE performance. 11 In the context of medical imaging, Marshall and Jones 12 reported that oral presentations and OSCEs provoked significantly more state anxiety in students than written examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Students' opinions regarding stress and anxiety associated with OSCEs have also been explored. 2,9,10 While OSCEs have been found to be more anxiety provoking than other assessments, 9,10 with students expressing concerns that heightened anxiety impacts OSCE performance, 2 the literature is mixed regarding the actual impact this anxiety has on OSCE performance. 11 In the context of medical imaging, Marshall and Jones 12 reported that oral presentations and OSCEs provoked significantly more state anxiety in students than written examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Objective Structured Clinical Examinations (OSCEs) have long been used to assess competencies in health professional education, such as medicine, nursing, and dentistry, where they have been demonstrated to be authentic, reliable, and valid (Gormley, Hodges, McNaughton, & Johnston, ; Newble, ). Both students and examiners have also recommended that incorporating OSCEs into clinical training in psychology would be beneficial (Sheen, McGillvray, Gurtman, & Boyd, ). Similarly, following positive reports from other health professional education providers, incorporating the use of simulated patients (SPs) in psychology training has been advocated (Gillaspy, Litzenburg, Leffingwell, & Miller, ; Johnson, Mastroyannopoulou, Beeson, Fisher, & Ononaiye, ).…”
mentioning
confidence: 99%
“…Importantly, there have been efforts to redress the dearth of simulation in psychology professional training. In Australia, OSCEs involving trained actors as SPs have been piloted in professional postgraduate psychology training programs (Sheen et al, ; Yap, Bearman, Thomas, & Hay, ). Both pilot projects recommended incorporating OSCEs into psychology curricula, with OSCEs subsequently introduced into postgraduate professional psychology programs at the University of Adelaide in 2015 as a method for trainees to demonstrate competencies in mental health assessment and the delivery of psychological intervention.…”
mentioning
confidence: 99%
“…In contrast, within clinical psychology and psychotherapy, the advantages of SPs are not fully exploited and have been recognized only in recent years [15][16][17][18][19]. Although using SPs in clinical psychology is perceived as important for learning, self-efficacy, self-reflection, and therapeutic alliance [15][16][17][18], current surveys concentrate on subjective assessments, small samples, or convenience samples or are limited to one-group designs [15][16][17][18].…”
Section: Simulated Patients In Clinical Psychologymentioning
confidence: 99%